Evaluation of the Community Response to HIV and AIDS : Learning from a Portfolio Approach - Rodriguez-García, Rosalía (Taylor and Francis, 2013)
While communities have played a large role in the HIV/AIDS response, their contributions and innovative approaches to HIV prevention, treatment, care and support have not always been the focus of systematic and rigorous evaluations. To address this gap, the World Bank led an evaluation of the impact of the community response to HIV, including country studies in Burkina Faso, India, Kenya, Lesotho, Nigeria, Senegal, South Africa and Zimbabwe over a three-year period. Due to the complexity and varied nature of community responses, the evaluation attempted to determine the results that investments have produced at the community level by applying a mixed method approach: Randomized Controlled Trials, quasi-experimental studies, qualitative studies and analytical studies including financial data. Specifically, the studies examined a typology of community response and the flow of funds to community-based organizations, while investigating the impact of the community responses on (1) knowledge and behavior, (2) use of services, (3) social transformation, and (4) HIV incidence. This editorial summarizes the results of this evaluation portfolio, finding that investments in communities have produced significant results, including, improved knowledge and behavior, and increased use of health services, and even decreased HIV incidence. Evidence on social transformation was more mixed, with community groups found to be effective only in some settings. Each study in the evaluation provides a partial view of how communities shape the local response; however, taken together they corroborate the common wisdom that communities can be a vital part of the global HIV/AIDS response.